Improving charge injection and charge transport in CuO-based p-type DSSCs-a quick and simple precipitation method for small CuO nanoparticles - Langmar, Oliver; Ganivet, Carolina R.; Schol, Peter; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael (Journal of Materials Chemistry C, 2018)
Herein, we introduce a co-precipitation synthesis of CuO, which produces small and uniform nanoparticles (∼12 nm) with a specific surface area of 97.3 m2 g-1. The resulting CuO nanoparticles are superior to the commercial ones, which have previously been used to prepare p-type DSSCs. In turn, we compared p-type DSSCs consisting of CuO-based photocathodes based on newly synthesized and commercial nanoparticles. Devices based on new CuO nanoparticles enable higher dye loadings, and, in turn, superior short-circuit current densities and efficiencies. To corroborate our findings, electrochemical impedance spectroscopy and intensity modulated photocurrent spectroscopy assays were conducted, revealing a better charge injection and faster charge transport for those photocathodes featuring the new CuO nanoparticles.
CRIS-Team Scopus Importer:2022-04-14